Znaczenie czasu w procesie radzenia sobie ze stratą sprawności - Brzezińska, Anna Izabela; Wolski, Paweł (My University, 2010)
Coping with ability loss is a process that is, on the one hand, highly dynamic, and on the other – characterised by signifi cant individual diversity. The theoretical premises of this research concept are based on the fi ve-stage model of coping with death developed by Elizabeth Kübler-Ross (2007). Our research enabled us to verify this concept and to single out – as a result of application of cluster analysis according to the BIC (Bayesian Information Criterion) – three phases of coping with ability loss, namely the struggle, depression and acceptance. Participants of the study were persons with various types of disabilities, divided into three groups: those with common disabilities (n=91), with uncommon ones (n=92) and those with complex disabilities (n=91). A battery of seven well-known standardised questionnaires was used, a structured interview and three questionnaires created specially for this study. Analysis of the results shows that persons with common types of disability remain in the struggling stage for 5 years after ability loss, and in 6-10 years – they are in depression or acceptance. Persons with complex and rare disabilities, owing to the high complexity of their problems, are characterised by vast variability with respect to these phases, and the amount of time they need before they reach the acceptance phase is highly dependent on outside factors, often ones beyond their control.
THE SIGNIFICANCE OF TIME IN THE PROCESS OF COPING WITH ABILITY LOSS
Keywords: radzenie sobie ze stratą; fazy radzenia sobie; niepełnosprawność rzadko występująca; niepełnosprawność sprzężona